A CONCEPTUAL FRAMEWORK FOR REPLACING AUDIT COMMITTEES WITH ARTIFICIAL INTELLIGENCE INFUSED BOT. Issue 3 (4th March 2021) - Dheeriya, Prakash; Singhvi, Meghna
Abstract: Due to advances in machine learning technology in recent years, artificial intelligence is becoming an increasingly viable replacement for human labor across a wide domain of business operations traditionally thought to be safe from the ever-widening reach of automation. We argue that one such function that may be an increasingly fitting candidate for such automation is the audit committee. In recent years, however, several shortcomings among prominent companies with regards to financial reporting quality have highlighted the weaknesses of audit committees and eroded billions in shareholder wealth. We offer a solution to the increasing problem of audit committee ineffectiveness in the modern business environment by proposing that the functions of audit committee be delegated to Artificial Intelligence infused bots. We find that such a system would have notable policy implications for shareholders, investors, regulators such as the SEC, and society at large.